Three decades of research efforts on the uses, conservation, and management of Cola nitida (Vent.): State of knowledge and prospects in Africa - Tokannou Isabelle E.T.; Sanogo Souleymane; Houndonougbo Juliano S.H.; Salako Kolawolé Valère; Fandohan Adandé Belarmain (Metsanduslikud Uurimused)
Cola nitida is a key multipurpose fruit tree species widely distributed across African countries. Several studies have investigated different aspects of the species, but there is a lack of synthesis on the current state of available literature and prospects for sustainable conservation and management of the species. Using the PRISMA approach for systematic review over the last three decades (1990–2022) in Africa, this study gathered key existing research findings on C. nitida. A total of 280 scientific publications were finally retained for this review. Several studies were focused on the socio-economic importance of the species (n = 139 ~ 50%), nutritional and chemical properties of its organs (n = 48 ~ 17%), improvement of its propagation methods (n = 30 ~ 11%), pest and pesticide control (n = 39 ~ 14%), morphological and genetic diversity (n = 21 ~ 7.5%), its botanical description and ecology (n = 2 ~ 0.7%), and climate change threats on the species (n = 1 ~ 0.3%). The review revealed a gap in knowledge on the methods for improving the species’ resilience to climate variability. Future research on the species should focus on its ecophysiological traits, the identification of elite accessions, and the type of agroforestry system that could optimize its productivity. The review provides a baseline for developing innovative management programs for C. nitida in Africa. Moreover, it highlights the need for more research efforts in the Central and East African native range of the species.